Description of the first Oriental species of the ant genus Xymmer (Hymenoptera: Formicidae: Amblyoponinae) - Satria, Rijal; Sasaki, Osamu; Viet, Bui Tuan; Oguri, Emiko; Syoji, Kazutaka; Fisher, Brian L.; Yamane, Sk; Eguchi, Katsuyuki (Zootaxa, 2016)
The monotypic ant genus Xymmer Santschi, 1914 was established for X. muticus (Santschi, 1914) which has so far been known only from the West African subregion. The genus is easily distinguishable from the other amblyoponine genera by the anteromedian part of clypeus which is produced as a short rectangular lobe. Additional undescribed species had been found exclusively from Madagascar and Africa until recently. However, in March, 2015, a Xymmer colony was found in northern Central Vietnam. In the present paper Xymmer phungi sp. nov. is described as the first Oriental species of the genus. Although the worker of X. phungi is morphologically quite similar to that of X. muticus, the former is distinguishable from the latter by the following two characteristics of the worker: clypeal lobe 1/6 times as long as broad (vs. 1/3 times as long as broad in X. muticus); anterior margin of the lobe weakly concave (vs. almost straight in X. muticus). Xymmer phungi is well distinguished from Ethiopian Xymmer spp. for which 28S sequences are available from GenBank. Our observations suggest that the species feeds on geophilids (Chilopoda: Geophilomorpha). An updated key to Vietnamese genera of the subfamily Amblyoponinae is also provided.